Enabling In Situ Studies of Metal-Organic Chemical Vapor Deposition in a Transmission Electron Microscope. (October 2022) - Tornberg, Marcus; Maliakkal, Carina B.; Jacobsson, Daniel; Wallenberg, Reine; Dick, Kimberly A.
Abstract: Abstract : The world of environmental microscopy provides the possibility to study and analyze transformations and reactions during realistic conditions to understand the processes better. We report on the design and development of a metal-organic chemical vapor deposition (MOCVD) system integrated with an environmental transmission electron microscope intended for real-time investigations of crystal growth. We demonstrate methods for achieving a wide range of precisely controlled concentrations of precursor gas at the sample, as well as for calibrating the sample partial pressure using the pressure measured elsewhere in the microscope column. The influences of elevated temperature and reactive gas within the pole-piece gap are evaluated with respect to imaging and spectroscopy. We show that X-ray energy-dispersive spectroscopy can be strongly affected by temperatures beyond 500 $^{° }$ C, while the spatial resolution is largely unaffected by heat and microscope pressure for the relevant conditions. Finally, the influence of the electron beam on the investigated processes is discussed. With this work, we aim to provide crucial input in the development of advanced in situ electron microscopy systems for studies of complex reactions in real time under realistic conditions, for instance as used during formation of semiconductor crystals.